2006
DOI: 10.1530/eje.1.02247
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing hormone physiology

Abstract: Corticotropin-releasing hormone (CRH), also known as corticotropin-releasing factor, is a highly conserved peptide hormone comprising 41 amino acid residues. Its name derives from its role in the anterior pituitary, where it mediates the release of corticotropin (ACTH) leading to the release of adrenocortical steroids. CRH is the major hypothalamic activator of the hypothalamic-pituitaryadrenal (HPA) axis. Major functions of the HPA include: (i) influencing fetal development of major organ systems including lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 39 publications
0
42
0
4
Order By: Relevance
“…CRH has existed, as an endogenous signaling molecule, even prior to the evolution of tetrapods and teleosts delineating its crucial role in the maintenance of the homeostasis of the organism. The hypophysiotropic CRH neurons are located in the parvicellular division of PVN (pPVN) in the hypothalamus and project to the external layer of the median eminence, releasing CRH into the hypophysial-portal circulation; however, some CRH fibers in the PVN also project to the brainstem [14] . Non-hypophysiotropic CRH neurons are abundant primarily in limbic structures, such as amygdala, locus coeruleus, involved in the procession of sensory information and in the regulation of the autonomic nervous system.…”
Section: Hypothalamic Corticotropin-releasing Hormonementioning
confidence: 99%
“…CRH has existed, as an endogenous signaling molecule, even prior to the evolution of tetrapods and teleosts delineating its crucial role in the maintenance of the homeostasis of the organism. The hypophysiotropic CRH neurons are located in the parvicellular division of PVN (pPVN) in the hypothalamus and project to the external layer of the median eminence, releasing CRH into the hypophysial-portal circulation; however, some CRH fibers in the PVN also project to the brainstem [14] . Non-hypophysiotropic CRH neurons are abundant primarily in limbic structures, such as amygdala, locus coeruleus, involved in the procession of sensory information and in the regulation of the autonomic nervous system.…”
Section: Hypothalamic Corticotropin-releasing Hormonementioning
confidence: 99%
“…Recently, a family of CRH-related peptides, termed the urocortins, has been identified. These peptides probably play a role in integrating multiple aspects of the stress-response, although their functions are largely unknown" [14].…”
Section: The Hpa Axismentioning
confidence: 99%
“…Although the exact inputs to the hypothalamus are not known, these neurons are largely controlled by serotoninmediated input from the amygdala and hippocampus of the limbic system [14]. It is interesting to note, again in passing, that serotonin is one of the key mono-amines depleted in depression.…”
Section: The Hippocampus Hypothalamus and Limbic Systemmentioning
confidence: 99%
“…The corticotropin-releasing hormone (CRH), also known as corticotropin-releasing factor (CRF), is a neuroendocrine peptide that regulates various physiological responses to stresses (Seasholtz et al, 2002). Moreover, CRH is considered to act as a neurotransmitter to coordinate various autonomic, hormonal, and behavioral responses to stresses and also may be involved in developmental processes (Muglia et al, 1995;Cortright et al, 1997;Majzoub, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that juvenile hormone, ecdysteriod and prothoracicotropic hormone are involved in the regulation of caste differentiation (Vitt and Hartfelder, 1998). Meanwhile, CRH regulates various hormonal and behavioral responses as a neurotransmitter in mammals (Majzoub, 2006). Considering that CRH which also functions as a crucial hormone in insect, we investigated the expression levels of AccCRH-BP among workers, queens, and drones of honeybees.…”
mentioning
confidence: 99%